Infrastructure Design for the People: Focus on the User – Exemplified by the Kienlesberg Bridge, Ulm. Issue 4 (2nd October 2021) - Akkermann, Jan; Halaczek, Bartlomiej; Knight, Martin; Vieth, Heinz-Josef
Abstract: In the realm of bridge construction, outstanding results that convince both engineering specialists as well as the general public are mostly the outcome of intense cooperation between clients, structural engineers and often architects. Particularly in the field of densely populated areas such as inner cities, urban planners as well as future users must be involved in the decision-making process. Kienlesberg Bridge is a successful example of this, from competition to commissioning. The multi-award-winning bridge for trams, pedestrians and cyclists crosses a broad rail area of Deutsche Bahn (German railway) at Ulm's central railway station. After a competition announcement in 2011, the bridge was developed in close cooperation between architects and structural engineers and built parallel to an underlying Deutsche Bahn construction site leading to its inauguration in 2018. The competition design already referred directly to the urban development situation. The elegant wave form results naturally from the interplay between the alignment, the force flow and the severe limits on possible pillar positions due to the complex construction site. In addition to its crossing function, the bridge offers a high quality of user environment thanks to its materials, lighting and equipment concepts. This creates a new urban space in inhospitable surroundings.